Do improviso às possibilidades de ensino: estudo de caso de uma professora de matemática no contexto da inclusão de estudantes cegos - Marcelly, L [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This qualitative research aims to explore possibilities of teaching mathematics for all, including blind students. Specifically, aims to investigate aspects proved as relevant to think about the teaching practice, in the context of inclusive education as advocated by Brazilian public policies. Therefore, a case study of the researcher own practice were conducted. The researcher worked as a mathematics teacher for ten years in the Brazilian public school system, in Sao Paulo state. The case consists in a presentation of the teacher, reporting three moments in her career. Firstly, stories about her first contact with a blind student in the context of inclusion; on the second moment, narratives about her experiences in an institution for people with disabilities, and the presentation of the case is ended with narratives of her recently own practice, after a few years of experience in inclusive schools. In this case study were highlighted aspects that had been proved as relevant to the teaching and learning practice in the context of inclusion, as follows: the construction and the use of manipulative materials for teaching and learning math; teachers training and working conditions in regular schools. These issues were discussed from the Brazilian legislation for inclusive education perspective, as well as literature on the educational use of manipulative material, universal design, assistive technology and teacher training. The results underscore the importance of using manipulative materials for teaching and learning mathematics, questioning the idea of adaptation, both didactical materials as curricula. The basis for this defense is to build didactical materials from the perspective of the universal design

Este texto apresenta uma pesquisa de natureza qualitativa cujo objetivo foi explorar possibilidades de ensinar matemática para todos, inclusive os estudantes cegos. De forma mais específica, investigar aspectos que se mostram relevantes para se pensar a prática docente no contexto da educação inclusiva, conforme defendida pelas políticas públicas. Para isso, foi realizado um estudo de caso da própria prática da pesquisadora, que atuou como professora de matemática por dez anos na rede pública de ensino. O caso é composto pela apresentação da professora e por relatos de três momentos de sua trajetória. No momento inicial, os relatos são sobre seu primeiro contato com um estudante cego no contexto da inclusão; no segundo momento, os relatos são sobre suas experiências numa instituição para pessoas com deficiência, sendo a apresentação do caso encerrada com relatos de sua prática nos últimos anos, após alguns anos de atuação em escolas inclusivas. Deste caso foram destacados aspectos que se mostraram relevantes para a prática docente no contexto da inclusão. São eles: a construção e o uso de materiais manipuláveis para o ensino de matemática; a formação do professor e as condições de trabalho na escola regular. Esses temas foram discutidos a partir da legislação brasileira para a educação inclusiva, bem como literatura sobre o uso educacional de materiais manipuláveis, desenho universal, tecnologia assistiva e sobre formação de professores. Os resultados ressaltam a importância do uso de material manipulável para a educação matemática, questionando a ideia de adaptação de currículo e de material. A base para essa defesa é a construção a partir da perspectiva do desenho universal
Keywords: Mathematics - Study and teaching; Matemática - Estudo e ensino; Educação inclusiva; Desenho universal; Cegos - Educação; Pratica de ensino